2019
DOI: 10.1371/journal.pntd.0006972
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Madariaga virus as a cause of acute febrile illness in children, Haiti, 2015-2016

Abstract: Madariaga virus (MADV), also known as South American eastern equine encephalitis virus, has been identified in animals and humans in South and Central America, but not previously in Hispaniola or the northern Caribbean. MADV was isolated from virus cultures of plasma from an 8-year-old child in a school cohort in the Gressier/Leogane region of Haiti, who was seen in April, 2015, with acute febrile illness (AFI). The virus was subsequently cultured from an additional seven AFI case patients from this same cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Appropriate medical care based on clinical presentation and laboratory studies was provided to study participants by clinic health care providers. Data on identification of arboviruses and other virus species among children participating in the study have been previously reported 22,23,25,26,[41][42][43][44] .…”
Section: Clinical Sample Collectionmentioning
confidence: 99%
“…Appropriate medical care based on clinical presentation and laboratory studies was provided to study participants by clinic health care providers. Data on identification of arboviruses and other virus species among children participating in the study have been previously reported 22,23,25,26,[41][42][43][44] .…”
Section: Clinical Sample Collectionmentioning
confidence: 99%
“…Human seroprevalence. Based on our PRNT results, the seroprevalence for MAYV, VEE complex alphavirus, UNAV, and MADV in people from Nueva Esperanza was 24% (17/70, 95% CI [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]), 16% (11/67, 95% CI [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]), 13% (6/48, 95% CI [6][7][8][9][10][11][12][13][14][15][16][17]…”
Section: Resultsmentioning
confidence: 99%
“…6 However, encephalitis cases and mild or asymptomatic cases mostly affecting children have been attributed to MADV recently in Venezuela, Haiti, and Panama. [7][8][9][10] Finally, although Una virus (UNAV) has been isolated from mosquitos of the Peruvian Amazon, it has been rarely associated with human disease. 11,12 Therefore, its distribution and the human disease risk in this region remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this epizootic also had 50 equine infections [85]. From 2015-2016, eight MADV infections were reported in a cohort of young school children in Haiti [130,131]. Similarly, in 2016, a single adolescent patient in Venezuela was diagnosed with MADV after demonstrating signs of a nonspecific febrile illness that was hypothesized to be due to recent travel to a locale that reported an equine epizootic of MADV [132].…”
Section: History Of Outbreaksmentioning
confidence: 99%